تأثير استخدام طرق التدريس على قدرة اللغة العربية لدى الطلبة - Dilly, Syeh; Suhaimi, Suhaimi; Hayati, Salma (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2021)
This study aims to determine how the influence of the use of learning methods on Arabic language skills for students. In order to achieve this goal,. The population in this study is 25 experimental research articles related to the discussion of this study. The research sample is 12 experimental research articles. Data analysis uses the Glass formula. The results of this study indicate that the use of methods in learning Arabic has a great influence based on analysis in 2017. Analysis of learning materials shows that Qiraah material has a greater influence than other materials. As for the analysis in terms of education level it is clear that the tsanawiyah madrasas have a larger effect size than the aliyah madrasas and universities. That way the use of methods is very effective for learning.